Propagation methods, agronomic practices and fruit production of Durio zibethinus L. in Malaysia : A review - Kamaruddin, Shamin-Shazwan; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Go, Rusea (Malaysian Nature Society, 2021)
Durio zibethinus L. (Durian) is a popular tropical fruit widely cultivated in Southeast Asian countries such as Malaysia, Thailand and Indonesia. It is renowned for its unique, intense aromatic fruits. Malaysia has been recognised as one of the world’s leading exporters of durian, particularly to China, owing to the cultivars that suit the taste of consumers both locally and abroad. This paper aims to provide information for future research in identification of cultivars, taxonomic identification, nutrient content and its utilisation from every plant parts. Local communities interests in durian plantation might benefit from this review as it highlighted useful recent agronomic practices and methods of propagation that help in assisting to improve yield of durian and market value. As the durian industry in Malaysia has acquired a great deal of interest in the local as well as international market, this review may also be beneficial to the entire community to obtain a more in-depth understanding of D. zibethinus.